Planejamento para o DLIS Desenvolvimento Local Integrado e Sustentável: o caso da Bacia do Jurumirim (Angra dos Reis, RJ) - Denise Maria Penna Kronemberger; Cacilda Nascimento de Carvalho; Judicael Clevelario Junior (Sociedade & Natureza)
The main goal of this research was to elaborate an Integrated Action Plan (IAC) for the sustain-able development of the Jurumirim Watershed (JW), considering the geo-economic relationships,the natural potentialities and vulnerabilities, as well as the intrinsic characteristics of the localcommunity, its demands and latencies. The JW has 70 km2 , and is located in the Angra dos Reiscounty, Rio de Janeiro state, Brazil. The objectives of IAC are income generation, improve environ-mental and community quality of life, through actions, named Pilot Projects (PP), that are articu-lated and reinforced. The PPs are the result of adequacy between community demands and ISLD objectives. The strategies to implement IAC and to guarantee its sustainability are: mobilize hu-man and financial resources to enable the projects, improve inhabitants association, build com-munity capacity, guarantee the negotiation and management on a participatory approach, em-power human and social capital, stimulate citizen participation and construct partnerships.